Phononic modulation of spin-lattice relaxation in molecular qubit frameworks - Aimei Zhou; Denan Li; Mingshu Tan; Yanpei Lv; Simin Pang; Xinxing Zhao; Zhifu Shi; Jun Zhang; Feng Jin; Shi Liu; Lei Sun (Nature Communications)
Abstract The solid-state integration of molecular electron spin qubits could promote the advancement of molecular quantum information science. With highly ordered structures and rational designability, microporous framework materials offer ideal matrices to host qubits. They exhibit tunable phonon dispersion relations and spin distributions, enabling optimization of essential qubit properties including the spin-lattice relaxation time (T 1) and decoherence time. In this study, through spin dynamic and vibrational spectroscopic characterizations of two radical-embedded framework materials, we show that hydrogen-bonded networks give rise to a low Debye temperature of acoustic phonons and generates sub-terahertz optical phonons, both of which facilitate spin-lattice relaxation. Whereas deuterating hydrogen-bonded networks reduces both phonon frequencies and T 1, eliminating such flexible structural motifs raises phonon dispersions and improves the T 1 by one to two orders of magnitude. The phononic tunability of spin-lattice relaxation in molecular qubit frameworks would facilitate the development of solid-state qubits operating at elevated temperatures.